2015
DOI: 10.1111/jch.12603
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Newly Diagnosed Hypertension Treated With the Renin Angiotensin Receptor Blocker Azilsartan Medoxomil vs Angiotensin‐Converting Enzyme Inhibitors: The Prospective EARLY Registry

Abstract: For patients with newly diagnosed hypertension, angiotensin‐converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) are usually the first‐line therapies. There is, however, no real‐life data regarding the relative clinical effectiveness and tolerability of either drug class. The prospective registry, Treatment With Azilsartan Compared to ACE Inhibitors in Antihypertensive Therapy (EARLY), was conducted to evaluate the effectiveness of the ARB azilsartan medoxomil (AZL‐M) vs ACE inhibitors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Roland E. Schmieder, MD; 1, * Peter Bramlage, MD; 2 for the EARLY Registry Group From the 1 Universit€ atsklinikum Erlangen, Erlangen, Germany; 2 Institut f€ ur Pharmakologie und pr€ aventive Medizin, Mahlow, Germany…”
Section: E T T E R T O T H E E D I T O Runclassified
“…Roland E. Schmieder, MD; 1, * Peter Bramlage, MD; 2 for the EARLY Registry Group From the 1 Universit€ atsklinikum Erlangen, Erlangen, Germany; 2 Institut f€ ur Pharmakologie und pr€ aventive Medizin, Mahlow, Germany…”
Section: E T T E R T O T H E E D I T O Runclassified
“…Azilsartan also improved the non-dipping pattern in nocturnal hypertension. Also can be combine with other anti-hypertensives like Chlorthalidione and or Amlodipine [12]. However, unlike other ARB's, Azilsartan is not backed up by clinical data supporting its ability to affect improvement in cardiovascular outcomes and is not approved for diabetic nephropathy or heart failure till date [14].…”
Section: Regional Estimates For the Prevalence Of Hypertensionmentioning
confidence: 99%
“…A starting dose of 20 mg may be considered for very elderly (aged more than 75 years) patients who may be at risk of hypotension [9]. Treatment of hypertensive patients using Azilsartan appears to be more effective in younger than in older patients [11,12].…”
Section: Regional Estimates For the Prevalence Of Hypertensionmentioning
confidence: 99%
“…We read with real interest the study by Schmieder and colleagues, 1 which provides important data on the efficacy of the angiotensin receptor blocker (ARB) azilsartan over the angiotensin-converting enzyme (ACE) inhibitor ramipril in blood pressure (BP) reduction in patients with hypertension. Furthermore, the authors showed greater decreases in BP in the patients with newly diagnosed hypertension vs the group with established hypertension, while target BP control was achieved more frequently in the first aforementioned group.…”
Section: To the Editormentioning
confidence: 99%
“…Furthermore, the authors showed greater decreases in BP in the patients with newly diagnosed hypertension vs the group with established hypertension, while target BP control was achieved more frequently in the first aforementioned group. 1 The potency of ACE inhibitors and ARBs in decreasing BP has been sufficiently proven; however, results from various studies have provided contradictory results on the efficacy of these agents in older vs younger patients. [2][3][4][5] We therefore believe that a subgroup analysis according to age would provide significant information about the management of hypertensive patients in real-life everyday clinical practice.…”
Section: To the Editormentioning
confidence: 99%